A música como arma de luta política: pontes entre a revista people's song, sindicatos e o partido comunista dos estados unidos - Arantes, Mariana Oliveira [UNESP] (My University, 2014)
This article analyses the People's Song magazine, relating the political engagement from its editors and contributors to some unions and the U. S. Communist Party. The magazine was a publication specialized in music, monthly printed between 1946 and 1949 in New York, with national distribution. Through the repertoire and the texts printed it was defended political positions of great importance in the national scenario of the period, as the defense of the people rights, considered the workers, the economically lower class of the population, discriminated minorities or by social class, gender or ethnicity.
Music as a political weapon: Bridges between the people's song magazine, unions and the u. S. Communist Party
Keywords: Music; Politics; United States